2009
DOI: 10.1177/0363546509346414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graft Selection on the Incidence of Postoperative Infection in Anterior Cruciate Ligament Reconstruction

Abstract: Hamstring tendon autografts have a higher incidence of infection than BPTB autografts or allografts. The use of allograft material in ACL reconstructions does not increase the risk of infection or the need for graft removal with infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
176
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(193 citation statements)
references
References 26 publications
14
176
1
2
Order By: Relevance
“…The present study is the first, to our knowledge, to establish diabetes as a risk factor for infection after ACL reconstruction, while the influence of graft choice is consistent with findings in previous studies 1,4 . Patient age and BMI did not influence the risk of postoperative infection after ACL reconstruction in this cohort, and there was insufficient evidence to establish an association between smoking and infection.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study is the first, to our knowledge, to establish diabetes as a risk factor for infection after ACL reconstruction, while the influence of graft choice is consistent with findings in previous studies 1,4 . Patient age and BMI did not influence the risk of postoperative infection after ACL reconstruction in this cohort, and there was insufficient evidence to establish an association between smoking and infection.…”
Section: Discussionsupporting
confidence: 92%
“…Maletis et al 4 reported an overall rate of infection of 0.48% after 10,626 ACL reconstructions, while Barker et al 1 reported a rate of 0.58% in 3126 patients. Judd et al 3 reported a rate of 0.68% in 1615 ACL reconstructions compared with an overall rate of 0.75% in 801 ACL reconstructions reported by Katz et al 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of graft selected for ACL reconstruction may increase the risk of infection, with several studies reporting a higher incidence of infection with hamstring tendon autografts compared with bone-patella-tendon-bone autografts and allografts [4,10,11].…”
Section: Introductionmentioning
confidence: 99%